The borders of criminal responsibility: difficult cases for the law's default understanding of people - Baron, Emily T. (Psychology, crime & law, 2019)
This paper provides an overview of the criminal justice system’s folk-psychological understanding of people and behavior. The attempt of this paper is to explore some of the complex literature focused on the criminal justice system in order to provide a concise account of its foundational beliefs about responsibility and the human condition. Although the effectiveness of the criminal justice system is a topic of contention, many scholars and legal actors agree that this institution is in part designed to impact people’s decisions and behavior. The law’s understanding of how people think and on what basis they act is thus of fundamental importance. This paper explores three areas where the law is willing to lessen prescription of criminal responsibility or finds a person not guilty despite their having engaged in apparently wrongful conduct. First, the law’s default understanding that people are rational agents is tempered by its acknowledgment of the human condition. Second, the law recognizes that some people who engage in wrongful conduct fall outside the ambit of criminal law. Third, the law embraces a more nuanced view of blame when determining appropriate punishment, taking into account the impact that an unfair social structure has on individual responsibility.